KESULITAN DIAGNOSIS DAN TERAPI PADA LIMFOMA PANKREAS DISERTAI SINDROMA KAUDA EQUINA - Ridwan, Muhammad; Dharmayuda, Tjokorda Gde (journal of internal medicine, 2008)
Lymphoma, part of non-Hodgkin’s lymphoma, is a rare malignancy in pancreas. Its clinicalpresentations and supporting laboratory and imaging results are similar to those of pancreas adenocarcinoma.Apart from pancreas, extranodal type of non-Hodgkin can involve many other organs including bone marrows,nervous system, and kidneys. Treatment should be focused on emergency priority and the underlying cause. Inthis case report, we have documented a 44 year-old man who initially presented jaundice and abdominal massand then diagnosed with pancreas tumor. However, pathology anatomy and histochemistry examinations ofperipancreas tissue biopsy and indicated a non-hodgkin lymphoma of pancreas, in form of diffuse large B celllymphoma, intermediate grade. The patient was developing cauda equina syndrome a week after laparotomy.Discussion among team suggested that both conditions may have the same root: lymphoma. The patient wasthen put on CHOP regiments of chemotherapy program and later, also underwent a spinal decompressionprocedure. Overall, jaundice, abdominal mass and other related symptoms subsided, and quality of lifeimproved, although some cauda equina symptoms remained.